Different Concentrations of FGF Ligands, FGF2 or FGF8 Determine Distinct States of WNT‐Induced Presomitic Mesoderm. (18th April 2016) - Sudheer, Smita; Liu, Jinhua; Marks, Matthias; Koch, Frederic; Anurin, Anna; Scholze, Manuela; Senft, Anna Dorothea; Wittler, Lars; Macura, Karol; Grote, Phillip; Herrmann, Bernhard G.
Abstract : Presomitic mesoderm (PSM) cells are the precursors of the somites, which flank both sides of the neural tube and give rise to the musculo‐skeletal system shaping the vertebrate body. WNT and FGF signaling control the formation of both the PSM and the somites and show a graded distribution with highest levels in the posterior PSM. We have used reporters for the mesoderm/PSM control genes T, Tbx6, and Msgn1 to investigate the differentiation of mouse ESCs from the naïve state via EpiSCs to PSM cells. Here we show that the activation of WNT signaling by CHIR99021 (CH) in combination with FGF ligand induces embryo‐like PSM at high efficiency. By varying the FGF ligand concentration, the state of PSM cells formed can be altered. High FGF concentration supports posterior PSM formation, whereas low FGF generates anterior/differentiating PSM, in line with in vivo data. Furthermore, the level of Msgn1 expression depends on the FGF ligand concentration. We also show that Activin/Nodal signaling inhibits CH‐mediated PSM induction in EpiSCs, without affecting T ‐expression. Inversely, Activin/Nodal inhibition enhances PSM induction by WNT/high FGF signaling. The ability to generate PSM cells of either posterior or anterior PSM identity with high efficiency in vitro will promote the investigation of the gene regulatory networks controlling the formation of nascent PSM cells and their switch to differentiating/somitic paraxial mesoderm. Stem Cells 2016;34:1790–1800